The 'dreaded PFO': anatomical and functional features of high risk for stroke. (8th October 2021) - Radico, Francesco; Foglietta, Melissa; Di Fulvio, Maria; Appignani, Marianna; Rossi, Serena; Angelis, Maria Vittoria De; Gallina, Sabina; Zimarino, Marco
Abstract: Patent foramen ovale (PFO) has a high prevalence in general population and can be implicated in cryptogenic stroke among young people. Recent trials have shown that transcatheter PFO closure is superior to medical treatment in the secondary prevention of ischaemic stroke. The benefit in the reduction of stroke recurrence is particularly evident in patients who have documentation of a PFO with high-risk characteristics. Therefore, after the assessment of a clear causal relationship with the event, a thoughtful documentation of anatomic (height, length, presence of an aneurysmatic or a floppy atrial septum, a prominent Eustachian valve or Chiari's network, an acute angle with the inferior vena cava) and functional high-risk characteristics is mandatory.